Ethnic disparities in mental health treatment gap in a community-based survey and in access to care in psychiatric clinics. (September 2014) - Nakash, Ora; Nagar, Maayan; Danilovich, Eli; Bentov-Gofrit, Daphne; Lurie, Ido; Steiner, Evelyne; Sadeh-Sharvit, Shiri; Szor, Henri; Levav, Itzhak
Background: Contrasting social status of ethnic groups differentially impacts the use of psychiatric services, including in Israel, despite its universal health system. However, relevant studies are limited. Aims: To examine ethnic differences in mental health treatment gap and in access to specialized care. Methods: Data were gathered from two sources. Study I included Mizrahi (Jews of North African/Asian origin, socially disadvantaged, n = 136) and Ashkenazi (Jews of European American origin, socially advantaged, n = 69) who were diagnosed with common mental disorders in the preceding 12 months in the Israeli component of the World Mental Health Survey. Study II included Mizrahi ( n = 133) and Ashkenazi ( n = 96) service users entering ambulatory mental health care. Results: Study I showed that the treatment gap was larger among Mizrahi compared with Ashkenazi respondents (28% standard error (SE) = 4.1 and 45% SE = 6.2, respectively, sought services) following adjustment for sociodemographic confounders (adjusted odds ratio (AOR) = 2.28, 95% confidence interval (CI) = 1.1–4.8). Study II showed that the access to specialized care lagged over a year among 40% of service users of both ethnic groups. No significant ethnic differences emerged in variables related to delay in accessing care. Conclusions: Treatment gap was larger among ethnically disadvantaged compared with the advantaged group. However, once in treatment, service users of both ethnic groups report similar barriers to care.